Uptake Rate of Cationic Mitochondrial Inhibitor MKT-077 Determines Cellular Oxygen Consumption Change in Carcinoma Cells - Chunta, John L.; Vistisen, Kerry S.; Yazdi, Zeinab; Braun, Rod D. (PLOS ONE, 2012)
Objective Since tumor radiation response is oxygen-dependent, radiosensitivity can be enhanced by increasing tumor oxygenation. Theoretically, inhibiting cellular oxygen consumption is the most efficient way to increase oxygen levels. The cationic, rhodacyanine dye-analog MKT-077 inhibits mitochondrial respiration and could be an effective metabolic inhibitor. However, the relationship between cellular MKT-077 uptake and metabolic inhibition is unknown. We hypothesized that rat and human mammary carcinoma cells would take up MKT-077, causing a decrease in oxygen metabolism related to drug uptake. Methods R3230Ac rat breast adenocarcinoma cells were exposed to MKT-077. Cellular MKT-077 concentration was quantified using spectroscopy, and oxygen consumption was measured using polarographic electrodes. MKT-077 uptake kinetics were modeled by accounting for uptake due to both the concentration and potential gradients across the plasma and mitochondrial membranes. These kinetic parameters were used to model the relationship between MKT-077 uptake and metabolic inhibition. MKT-077-induced changes in oxygen consumption were also characterized in MDA-MB231 human breast carcinoma cells. Results Cells took up MKT-077 with a time constant of ∼1 hr, and modeling showed that over 90% of intracellular MKT-077 was bound or sequestered, likely by the mitochondria. The uptake resulted in a rapid decrease in oxygen consumption, with a time constant of ∼30 minutes. Surprisingly the change in oxygen consumption was proportional to uptake rate, not cellular concentration. MKT-077 proved a potent metabolic inhibitor, with dose-dependent decreases of 45–73% (p = 0.003). Conclusions MKT-077 caused an uptake rate-dependent decrease in cellular metabolism, suggesting potential efficacy for increasing tumor oxygen levels and radiosensitivity in vivo.